Genetic Variability and Correlation Coefficient for Fodder Yield and its Components in Forage Pearl Millet Hybrids under Rainfed Conditions of Gujarat - Dhedhi, K. K.; Ansodariya, V. V.; Chaudhari, N. N.; Sanghani, J. M.; Sorathiya, J. S. (International Journal of Bio-resource and Stress Management, 2016)
The 29 forage pearl millet hybrids were studied for genetic variability, heritability, genetic advance and character association of green fodder yield and its components at Jamnagar and Dhari centers of Junagadh Agricultural University, Gujarat under rainfed conditions during kharif, 2014. The analysis of variance revealed highly significant differences among the hybrids for all the characters studied except lodging score and harvest index. Wide range of phenotypic variability was observed for green fodder yield plant-1, dry fodder yield plant-1 and plant height, indicating the scope for genetic improvement through selection and other breeding methods. PCV and GCV estimates were found to be high to moderate for harvest index (33.49%, 25.68%), lodging score (34.16%, 20.77%), grain yield plant-1 (29.63%, 20.96%), dry fodder yield plant-1 (26.49%, 20.42%) and green fodder yield plant-1 (23.44%, 16.45%) which suggests that there is enough scope for selection. Broad sense heritability ranged from 37.00% (lodging score) to 81.60% (plant height). The high heritability coupled with high to moderate genetic advance expressed as percentage of mean was observed for plant height (81.60%, 23.84%), harvest index (58.80%, 40.58%), dry fodder yield plant-1 (59.40%, 32.43%) and grain yield plant-1 (50.10%, 30.55%) which showed that these traits were controlled by additive gene effects and phenotypic selection were for these traits were likely to be effective. Correlation analysis revealed that green fodder yield plant-1 had significant positive association with dry fodder yield plant-1 (0.962, 0.926) and days to maturity (0.483, 0.395) at both genotypic and phenotypic levels, and days to 50% flowering (0.612) and plant height (0.490) at genotypic level only. Hence, these characters would be more effective for boosting green fodder yield performance of forage pearl millet hybrids.